Robotic arm control based on human arm motion - Tze How D.N.; Keat C.W.; Anuar A.; Mohamed Sahari K.S. (Springer Verlag, 2023)
This paper discusses the development of a robotic arm whereby its motion is controlled based on the movements of the human arm. There are three major components in this project. They are a wearable control device, microcontroller and robotic arm. The wearable control device acts as a sensor to translate the physical movement of the human arm into electrical signals. The translated signals in the form of positional data are sent to the microcontroller unit for processing. The microcontroller unit processes the signals and outputs it to the robotic arm as physical replicated movements. The wearable control device is capable of sensing six degrees of freedom by the human arm joints movements. This includes rotation of the shoulder, arm, bending of the shoulder, elbow, wrist, and gripping motion. The fabricated robotic arm is able to perform six different motions replicating and mimicking the motions of the human arm. © 2014 Springer Science+Business Media Singapore.